Memorial dedicated to Katherine Kirkpatrick - Ghosh, Ayan (2023)
Memorial dedicated to Katherine Kirkpatrick, wife of Major General James Kirkpatrick, Commander of Horse, Madras Army. She was mother to James Achilles Kirkpatrick, who later served as a Company Resident at Hyderabad (Deccan) from 1798 until 1805. Another son, William Kirkpatrick, also served as a Company Resident at Hyderabad. Katherine was born at Fort St. George (Chennai) on 22nd September 1744 and died there on 27th January 1766, at age 22.